Functional performance deficits in adolescent athletes with a history of lateral ankle sprain(s). (September 2018) - Ko, Jupil; Rosen, Adam B.; Brown, Cathleen N.
Abstract: Objective: To determine if adolescent athletes with a history of lateral ankle sprain(s) (LAS) displayed deficits on functional performance tests (FPTs) and if deficits on FPT were related to the number of previous LAS. Design: Cross-sectional study. Setting: Biomechanics Laboratory. Participants: The injured group (n = 24) had a history of ≥1 moderate-severe LAS. The uninjured group (n = 34) had no history of LAS. Main outcome measure(s): The average reach distance of three trials in each direction of the star excursion balance test (SEBT) was normalized to leg length (%). The average of two trials of single-leg-hop test (SLHT) was calculated in seconds. Results: The injured group performed significantly worse in 3 directions of SEBT than the uninjured group (P < 0.05). SLHT was significantly slower in the injured group compared to the uninjured group (P < 0.05). Statistically significant, strong to moderate inverse relationships were found between the numbers of LAS and each of the three directions of the SEBT (P ≤ 0.01). No relationship was revealed between the number of LAS and the SLHT (P > 0.05). Conclusion(s): Adolescent athletes with a history of LAS exhibit functional performance deficits on the SEBT and SLHT. Therefore, the SEBT and SLHT may provide clinicians cost- and time-effective objective tools. Highlights: The injured group performed significantly shorter reaches in the SEBT. The injured group demonstrated a significantly slower time to complete the SLHT. Moderate inverse relationships between the SEBT and number of ankle sprain.